Houston Hartsfield Holloway papers - Holloway, Houston Hartsfield, 1845-1917.
Holograph autobiography in which Holloway recounts his life as a slave in Meriwether and Pike counties, Georgia, before and during the Civil War, and as a blacksmith and African Methodist Episcopal clergyman during the Reconstruction era and through 1910. Holloway's recollections include work chants, hymns, and social customs from his years as a slave and his work organizing congregations and building churches as a clergyman in Georgia. Includes a note (1932) regarding the autobiography, photocopies of the autobiography and note, and a photocopy of a photograph (1894) of Holloway.
Slave prior to the Civil War and emancipation and later a blacksmith and clergyman from Georgia.
Collection material in English.
Keywords: African Methodist Episcopal Church -- Georgia; African Americans -- Music; African Americans -- Social life and customs; African Americans -- Georgia; Blacksmithing -- Georgia; Slavery -- Georgia; Slaves. -- Georgia; Meriwether County (Ga.) -- History; Pike County (Ga.) -- History; Blacksmiths; Clergy; Slaves -- Georgia